Peran Kepala Madrasah Pasca Pandemi Covid-19: Kajian Integrasi Manajemen Pendidikan dan Kecerdasan Sosial Perspektif Islam - Faisal Faliyandra; Azisi; Fathor Rosi (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
The increase in the use of social media during the Covid-19 period allows it to reduce the social sense of the community in the educational environment. So school principals have a tough task how to manage school units by implementing good education administration in the post-Covid-19 era. So the purpose of this paper is to examine various kinds of literature (books, journals) on how education administration is integrated with social intelligence from an Islamic perspective in order to find a good concept of maintaining public relations in the school environment after the pandemic. The results show that ; 1) Social intelligence from an Islamic perspective that can be integrated such as compassion for fellow human beings, sincerity, kindness, helping others, and friendship with fellow human beings; 2) The way the principal interacts must be based on indicators of social intelligence from an Islamic perspective (compassion for fellow human beings, sincerity, kindness, helping others, and friendship with fellow humans). The implementation of administration that is integrated with social intelligence from an Islamic perspective is not only to improve good relations between humans (Hablum Minannas), but also to seek the pleasure of Allah SWT (Hablum Minallah).